The Role of Socio-Cultural Competence in Developing Teachers’ Aesthetic Taste - Muzropova Guljamol Mardonovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the role of socio-cultural competence in shaping teachers’ aesthetic taste. Socio-cultural competence encompasses knowledge, skills, and attitudes that enable educators to understand, appreciate, and respond appropriately to cultural and social contexts. Developing aesthetic taste is an essential component of professional pedagogical competence, allowing teachers to foster artistic sensitivity, critical perception, and cultural awareness in themselves and their students. The study highlights pedagogical strategies, theoretical approaches, and practical methods for integrating socio-cultural competence into the development of aesthetic taste. By engaging with diverse art forms, cultural traditions, and creative practices, teachers enhance their ability to perceive aesthetic qualities, interpret artistic works, and cultivate culturally responsive teaching. The article emphasizes that socio-cultural competence serves as a foundation for aesthetic education, moral development, and the creation of inclusive and culturally rich learning environments.